Ethnomathematics: Exploration of Geometry in Building Design Jatisobo Grand Mosque - Ajizah; Susilowati, Dewi (Jurusan Pendidikan Matematika FKIP Universitas Halu Oleo, 2025)
Ethnomathematics is a learning innovation that combines the concepts of culture and mathematics in it. The purpose of this research is to explore and describe the design of the Jatisobo Great Mosque building in Sukoharjo district which has geometry concepts in it. Jatisobo Great Mosque is one of the oldest mosques and has also been designated as a cultural heritage in Sukoharjo district. Furthermore, the type of research uses qualitative research through an ethnographic approach. Then the research method uses 3 ways, namely surveys, interviews and documentation. With technical data analysis using Spradley's model through four stages namely domain analysis, taxonomy analysis, componential analysis and cultural theme analysis. This study shows the results that in the building design of the Great Mosque Jatisobo Sukoharjo district there is the concept of geometry. Geometry concepts such as flat shapes (square, rectangle, circle and triangle), space (pyramid, prism and tube), geometry transformation (reflection and dilation) and angle. These geometry concepts are found in the form of room plans, mosque roofs, mosque windows, mosque doors, supporting corners, drum, horns, and mosque poles, among others.